Endogenous Borrowing Constraints with Incomplete Markets - Zhang, Harold H. (Journal of Finance, 1997)
This article develops ways to endogenize the borrowing constraints used in a class of computable incomplete markets models. We allow the constraints to depend on an investor's characteristics such as time preference, risk aversion, and income streams. The proposed constraint can be interpreted as a borrowing limit within which an investor has no incentive to default. Using a numerical algorithm, we find that for an array of structural parameters, the endogenous borrowing constraints can be much less stringent than the ad hoc borrowing constraints adopted by the existing studies.